Organization and evolution of the actin gene family in sea urchins. - Johnson, P J (1983)
Genomic libraries of the sea urchins Strongylocentrotus franciscanus and Lytechinus pictus were screened with an actin cDNA clone from Strongylocentrotus purpuratus. Four nonoverlapping clones were isolated and characterized from the S. franciscanus library; three were isolated and characterized from the L. pictus library. Linked genes having the same transcriptional orientation were found on all S. franciscanus clones. Three clones contained two actin genes each; the other clone contained three. In contrast, the L. pictus clones contained only one actin gene. Comparison of actin genomic clones from these three species indicated a difference in the genomic organization of sea urchin actin genes in that the genes appear to be more highly clustered in S. franciscanus than in S. purpuratus and L. pictus. Genomic dot blots and reassociation kinetics demonstrated that the copy number of actin genes in all three species is 15 to 20. Nucleotide sequence homology of actin genes within and among the species was measured by thermal elution. These experiments indicated that there is a high degree of interspecies actin gene sequence homology but that, within each species, actin gene sequences may differ by as much as 30%. Sequencing of two S. franciscanus actin genes revealed introns at the same amino acid positions, 121 and 204, reported for S. purpuratus actin genes. These data demonstrated that the genomic copy number, the transcriptional orientation of linked genes, and, to the extent studied, the intron position of actin genes have evolved similarly in these three species. In contrast, significant change has occurred in the chromosomal arrangement of sea urchin actin genes.